Spirituality and religiousity in the experience of suffering, guilt, and death of the elderly with cancer - Raniele Araújo de Freitas; Tânia Maria de Oliva Menezes; Lucivalda Barbosa Santos; Halanna Carneiro Guimarães Bastos Moura; Marta Gabriele Santos Sales; Fabiana Araújo Moreira
ABSTRACT Objective: to understand spirituality and religiosity in the experience of suffering, guilt, and death of the elderly with cancer. Method: qualitative research based on Viktor Frankl's Existential Analysis. Twenty phenomenological interviews were conducted with people over 60 years old undergoing chemotherapy treatment at an oncology unit of a hospital in the city of Salvador, Bahia State, Brazil, between August and October 2018. Results: the following categories emerged: Experiences spirituality and religiosity in the face of the tragic triad and existential emptiness; Uses spirituality/religiosity as resilience strategies. After apprehension of ontic aspects, it was possible the ontological understanding of spirituality and religiosity in the face of suffering, guilt, and death experienced in the elderly with cancer's daily life. Final considerations: spirituality and religiosity were understood as coping strategies used in the unstable experience of the elderly with cancer, providing comfort and resilience.